REALISASI PENGENDALI ON-OFF HISTERISIS DENGAN OPERATIONAL AMPLIFIER (OP-AMP) - Tadeus, Dista Yoel; Subari, Arkhan; Manan, Saiful (Gema Teknologi, 2018)
The realization of the On-Off control system can be built using the comparator principle. The principle has a weakness that is the possibility of chattering due to 'thin' limit of comparator switching. Low immunity to noise increases chances of chattering, if not anticipated it will cause 'fatigue' on actuator thus reducing component’s lifetime. Hysteresis has features to suppress chattering. This article describes how to realize the hysteresis On-Off controller using Operational Amplifier (Op-Amp) which is simple and cheap discrete electronics component, by modifying the Op-Amp comparator circuit so that it has the hysteresis band with minimum and maximum limit variable so that the reference point of the comparator can be shifted.